Numerical study of the transverse localization of waves in one-dimensional lattices with randomly distributed gain and loss: effect of disorder correlations - Nguyen, Ba Phi; Lieu, Thi Kim Thoa; Kim, Kihong (Waves in Random and Complex Media, 2022)
We study numerically the effects of short- and long-range correlations on the localization properties of the eigenstates in a one-dimensional disordered lattice characterized by a random non-Hermitian Hamiltonian, where the imaginary part of the on-site potential is random. We calculate the participation number versus strengths of disorder and correlation. In the short-ranged case and when the correlation length is sufficiently small, we find that there exists a critical value of the disorder strength, below which enhancement and above which suppression of localization occurs as the correlation length increases. In the region where the correlation length is larger, localization is suppressed in all cases. Similar behavior is obtained for long-range correlations as the disorder strength and the correlation exponent are varied. Unlike in the case of a long-range correlated real random potential, no signature of the localization transition is found in a long-range correlated imaginary random potential. In the region where localization is enhanced in the presence of long-range correlations, we find that the enhancement occurs in the whole energy band, but is strongest near the band center. In addition, we find that the anomalous localization enhancement effect occurs near the band center in the long-range correlated case.
Keywords: Correlation exponents; Correlation lengths; Enhancement effects; Localization properties; Long range correlations; Non-Hermitian Hamiltonians; One-dimensional lattice; Randomly distributed; Anderson localization; long-range correlation; non-Hermiticity; participation number; short-range correlation